'Isolated' germline mosaicism in the phenotypically normal father of a girl with X-linked hypophosphatemic rickets. Issue 1 (January 2020) - Lin, Yunting; Cai, Yanna; Xu, Jianan; Zeng, Chunhua; Sheng, Huiying; Yu, Yang; Li, Xiuzhen; Liu, Li
Abstract : Objective: X-linked hypophosphatemic rickets (XLHR) is the most common form of inherited rickets caused by pathogenic variants of PHEX gene with an X-linked dominant inheritance pattern. Precise molecular diagnosis of pathogenic variant will benefit the genetic counseling and prenatal diagnosis for the family with XLHR. Here, we presented an 'isolated' germline mosaicism in the phenotypically normal father of a girl with XLHR. Methods and results: For the initial molecular screen of PHEX gene, DNA samples of the proband and her parents were extracted from their peripheral blood samples respectively. Sanger sequencing found a ' de novo ' novel heterozygous variant, c.1666C>T(p.Q556X), at the PHEX gene in the proband, but not in her phenotypically healthy parents. Due to an occasional abnormality of his serum phosphate previously, further examinations for the father were taken to exclude the possibility of paternal mosaicism. Eight samples from different tissues were analyzed for PHEX gene by Sanger sequencing. Surprisingly, one 'isolated' germline mosaicism was detected only in his sperm with an estimated frequency of 26.67%. The mosaic allele was identical to the c.1666C>T(p.Q556X) variant in the proband. Conclusions: This is the first case of 'isolated' germline mosaicism with pathogenic PHEX variant. Our study provides accurate diagnosis and valuable counseling for this family. This report also alerts clinicians and geneticists to exclude the possibility of the isolated germline mosaicism and prevent intrafamilial recurrences of inherited diseases.